2003
DOI: 10.1016/s0375-9474(03)01229-6
|View full text |Cite
|
Sign up to set email alerts
|

The structure of nuclear systems derived from low momentum nucleon–nucleon potentials

Abstract: Various nuclear structure observables are evaluated employing low-momentum nucleonnucleon (NN) potentials V low−k derived from the CD-Bonn and Nijmegen NN interactions V N N . By construction, the high momentum modes of the original V N N are integrated out in V low−k , with the requirement that the deuteron binding energy and low energy phase shifts of V N N are exactly reproduced. Using this interaction, we evaluate the bulk properties (binding energy and saturation density) of nuclear matter and finite nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 33 publications
13
76
0
Order By: Relevance
“…By solving the Yakubovsky equations we can calculate the binding energy of 4 He. A similar tendency of the Λ dependence for 3 H can be also seen in the results for 4 He. In Fig.…”
Section: Figsupporting
confidence: 85%
See 1 more Smart Citation
“…By solving the Yakubovsky equations we can calculate the binding energy of 4 He. A similar tendency of the Λ dependence for 3 H can be also seen in the results for 4 He. In Fig.…”
Section: Figsupporting
confidence: 85%
“…Kuckei et al [4] investigated the nuclear matter and the closed-shell nucleus 16 O by using the LMNN interaction obtained by Bogner et al They concluded that the LMNN interaction can be a very useful tool for low energy nuclear structure calculations, and one should be cautious if the observable of interest is sensitive to the single-particle spectrum at energies above the cutoff momentum.…”
Section: Recently Bogner Et Almentioning
confidence: 99%
“…Our special attention was focussed on isospin T = 1 pairing for nucleon pairs with total momentum equal to zero in the 1 S 0 partial wave like in an earlier approach in a spherical box [8]. Using the standard BCS approach the pairing gap ∆ k for pair of nucleons with momenta k and −k is obtained by solving the gap equation [27] …”
Section: Pairing Correlationsmentioning
confidence: 99%
“…This misconception still persists and has recently led to the conclusion that low-momentum two-nucleon interactions are "wrong" since they do not give saturation in nuclear matter and finite nuclei are overbound for lower cutoffs [17,18]. The missing physics that invalidates this conclusion is many-body forces, which were completely neglected in those studies.…”
Section: Introductionmentioning
confidence: 99%